Методологічні засади визначення траєкторій економічної реконструкції територій в умовах тривалих загроз - Amosha, Oleksandr I.; Soldak, Myroslava O. (Institute of Industrial Economics of NAS of Ukraine, 2026)
Based on the theoretical foundations of evolutionary economic geography and the concept of resilience, a methodological framework for identifying trajectories of economic reconstruction of territories is proposed. The framework is grounded on understanding historical heritage, capturing manifestations of resilience in the present, and shaping a vision of the future based on a combination of economic, social, and environmental values. This perspective allows the reconstruction of Ukrainian territories to be viewed not as a pre-designed process, but as a dynamic response to prolonged military threats and a high degree of uncertainty, in which adaptability and local innovative activity emerge as key drivers of structural transformation.It is shown that dependence on previously established industrial paths, institutional lock-ins, and regulatory barriers have constrained the emergence of new local innovation trajectories in Ukraine, thereby limiting the capacity of territories to respond to the polycrisis associated with large-scale military threats. At the same time, elements of historical legacy—such as sectoral structures, professional communities, educational institutions, production chains, and resilient social networks—can be considered a starting point for the formation of new trajectories of economic reconstruction.The importance of complementing formal institutional solutions with attention to emerging resilience is substantiated, understood as the capacity of communities for self-organization, creative response, and the development of new practices in the face of existential challenges. It is further argued that contemporary industrial culture shaped around the concept of DIY 4.0 opens new opportunities for broad citizen participation in local-level structural transformations on an innovation-driven basis. Production spaces such as FabLabs and RoboLabs combine elements of education, digital manufacturing, experimental entrepreneurship, and social cohesion—components that are critically important for reconstruction oriented toward wartime and post-war challenges. Such spaces not only contribute to strengthening human capital but also provide a foundation for transforming regional industrial ecosystems into systems capable of generating and sustaining new development trajectories under conditions of profound structural change.